Digitalization of MSMEs Businesses in Boalemo Regency: Strategies and skills enhancement - Ade Yusupa; Aditya Lapu Kalua; Victor Tarigan (Universitas Muhammadiyah Magelang, 2024)
In the current digital era, many MSME players in Boalemo Regency still employ conventional methods in marketing their products. The objective of this service activity is to assist MSME players in enhancing their skills and knowledge regarding business digitalization. The methods utilized in this service activity include training sessions and post-training mentoring. Training is conducted through discussion sessions with instructors and assistance in integrating businesses into the digital realm. The results of this service activity indicate that 50 participants from MSMEs have successfully improved their skills and knowledge regarding business digitalization, such as registering their business legality with the Business Identification Number (BIN), creating a Google Business Profile, and creating digital promotional photos or videos using Canva. The majority of partners have successfully completed the training program and have shown significant progress in transitioning their businesses into the digital world.